2021
DOI: 10.1136/injuryprev-2020-044092
|View full text |Cite
|
Sign up to set email alerts
|

Predicting drowning from sea and weather forecasts: development and validation of a model on surf beaches of southwestern France

Abstract: ObjectiveTo predict the coast-wide risk of drowning along the surf beaches of Gironde, southwestern France.MethodsData on rescues and drownings were collected from the Medical Emergency Center of Gironde (SAMU 33). Seasonality, holidays, weekends, weather and metocean conditions were considered potentially predictive. Logistic regression models were fitted with data from 2011 to 2013 and used to predict 2015–2017 events employing weather and ocean forecasts.ResultsAir temperature, wave parameters, seasonality … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…This will also allow inclusion of more weekday data. Indeed, with only nearly nine weeks of data, our findings on the influence of weekday on beach attendance (Figure 5d) are unclear while previous work showed that weekday is important to life risk at the beach [61]. Given our understanding in rip current dynamics, previous modelling work and the relative alongshore uniformity of bar/rip morphology, developing an hourly or daily rip current hazard predictor based on wave and tide predictions should be relatively straightforward.…”
Section: Discussionmentioning
confidence: 77%
“…This will also allow inclusion of more weekday data. Indeed, with only nearly nine weeks of data, our findings on the influence of weekday on beach attendance (Figure 5d) are unclear while previous work showed that weekday is important to life risk at the beach [61]. Given our understanding in rip current dynamics, previous modelling work and the relative alongshore uniformity of bar/rip morphology, developing an hourly or daily rip current hazard predictor based on wave and tide predictions should be relatively straightforward.…”
Section: Discussionmentioning
confidence: 77%
“…This will also allow inclusion of more weekday data. Indeed, with only nearly nine weeks of data, our findings on the influence of weekday on beach attendance (Figure 5d) are unclear while previous work showed that weekday is important to life risk at the beach [60]. Given our understanding in rip current dynamics, previous modelling work and the relative alongshore uniformity of bar/rip morphology, developing an hourly or daily rip current hazard predictor based on wave and tide predictions should be relatively straightforward.…”
Section: Surfzone Life Riskmentioning
confidence: 77%